Luminescence of praseodymium doped perovskite - like SrLa₄Ti₅O₁₇ under excitation with VUV and UV synchrotron radiation - Nedilko, S.G.; Chumak, V.; Titov, Yu. (Functional Materials, 2018)
The wide-band complex spectra of intrinsic luminescence of undoped SrLa₄Ti₅O₁₇ compounds are found in range of 350-1100 nm under excitation by the light from ultraviolet and vacuum ultraviolet range (50-334 nm) of synhrotron radiation. The possible origines of the observed luminescence are associated with peculiarities of the structure of the layered perovskite-like SrLa₄Ti₅O₁₇ compound. So, three luminescence components of the intrinsic luminescence peaked near ~ 530, ~ 830, and ~ 1100 nm have been attributed to the radiation decay of excitons localized on (TiO₆)⁸⁻ molecular groups of three ypes in the lattice of SrLa₄Ti₅O₁₇. The luminescent features related with 4f→4f and 4f5d→4f radiation transitions in Pr³⁺ ions are found in addition to mentioned intrinsic emission for the SrLa₄Ti₅O₁₇ compound doped with Pr³⁺ ions. Obtained results show the prospects of the SrLa₄Ti₅O₁₇ compounds doped with Pr³⁺ ions to be used as luminophores of wide emission spectra.